Studi Perbandingan Kemampuan Nannochloropsis sp. dan Spirulina sp. sebagai Agen Bioremediasi Terhadap Logam Berat Timbal (Pb) [Comparative Study Of Ability Nannochloropsis sp. And Spirulina sp. As Agent Bioremediation Of Heavy Metal Plumbum (Pb) ] - Endang Dewi Masithah; Boedi Setya Rahardja; Khilyatun Nisak (Faculty of Fisheries and Marine Universitas Airlangga, 2013)
Abstract Microalgae species Nannochloropsis sp. can used as heavy metal biosorben because of it's adsorption capability that caused by the active cluster which contained in that species (Sembiring et al., 2008). Chlorella sp. is one of phytoplankton species that has the bioaccumulation ability of heavy metals and easily cultivated (Arifin, 1997). Lead (Pb) is a mineral belonging to microelements, is a heavy metal and is a potentially toxic material. Water bodies that have been polluted by compounds or ions Pb because can lead to the death of aquatic biota, the number of Lead (Pb) present in water bodies exceeding the proper concentration (Palar, 2004). One way to anticipate the increasing heavy metal pollution in the water is to bioremediation. The research using experimentally, the research design used was completely randomized design (CRD) consisting of four treatments with five replications. The concentrations of heavy metals Plumbum (Pb) used is 0 ppm and 0.9 ppm. The main parameters in this study is the ability of bioremediation Plumbum (Pb) by Nannochloropsis sp. and Chlorella sp. SPSS analytics normality test results and test the ability of T 95% in Nannochloropsis sp. and Chlorella sp. in absorbing heavy metals Plumbum (Pb) concentrations of 0 ppm and 0.9 ppm indicate that the data is normal and the results obtained were significantly different / significant. While the analysis of SPSS test T on heavy metal absorption capability comparison Plumbum (Pb) concentration of 0 ppm and 0.9 ppm by Nannochloropsis sp. and Chlorella sp. showed that the results were not significantly different / non significant. On average results obtained, Nannochloropsis sp. have a higher capacity than Chlorella sp. in the bioremediation process of heavy metals Plumbum (Pb).